If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(1 + -1b) = -11 + 6b (1 * -1 + -1b * -1) = -11 + 6b (-1 + 1b) = -11 + 6b Solving -1 + 1b = -11 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. -1 + 1b + -6b = -11 + 6b + -6b Combine like terms: 1b + -6b = -5b -1 + -5b = -11 + 6b + -6b Combine like terms: 6b + -6b = 0 -1 + -5b = -11 + 0 -1 + -5b = -11 Add '1' to each side of the equation. -1 + 1 + -5b = -11 + 1 Combine like terms: -1 + 1 = 0 0 + -5b = -11 + 1 -5b = -11 + 1 Combine like terms: -11 + 1 = -10 -5b = -10 Divide each side by '-5'. b = 2 Simplifying b = 2
| 0=4x^2-12x+5 | | y=-.8(0)+2 | | 32-4(x-6)=-2 | | t=9x+6 | | 2(4x+9)=16x+15-8x+3 | | 3x+18-17=41 | | 3(x+4)=8x+8-5x+4 | | 7(4x-3)=-6x+3(3+8x) | | 2(m+5)=5m+6-m | | (9x+2)(8x^2+7x+1)= | | 5x+2y=785+3280 | | -4n=1/3 | | 5-7x=24-14x | | x+4066=10546 | | -2(2+x)+4(1+8x)=8x+6x | | 4x^3-17x^2-4x=-2 | | 4-5x=-24 | | 8x+32x-6=10(4x+5) | | x+2+20x+100=0 | | 5x+2=-6 | | -2=4(0)+y | | 4x+12=-1088x | | w+1.9=5.56 | | 4x^3-17x^2-4x+2=0 | | 3x/4=-y | | -2=4x+0 | | 5+2y=-6 | | 36-(2c+4)=2(c+6)+c | | 15b+5b=960 | | -8(n+2)=-4(3n-2) | | x+2(0)=-2 | | x^3-8x^2+16x+957=0 |